Design and Development of a Student Assessment Application Based on Android Using the Waterfall Model - Muhammad Zulfikar Sachori Putra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
SD Negeri Samudra Jaya 01 in Kramat Village, Tarumajaya Subdistrict, Bekasi, implements the 2013 curriculum and currently assesses students using Excel. However, manual data processing and no integrated system slow the process and increase errors. Motivated by these limitations, this research developed an Android?based student assessment application with Java and XML in Android Studio. It employs a MySQL database on Serv00.com with PHP?APIs and JSON. UML diagrams ensured a structured system architecture, while development followed the Waterfall methodology and the interview method with the school principal and teachers. Functionality was validated with BlackBox testing, achieving a 99.8% data accuracy rate, API response times under two seconds, and 92% teacher satisfaction during User Acceptance Testing. AES encryption secures both data at rest and in transit, ensuring enhanced security and compliance with the 2013 curriculum. Compared to the previous spreadsheet?based system, the app reduced administrative workload by 40%, enabling teachers to input grades, calculate scores, generate automated reports, and share results via smartphones before report card distribution. Stakeholders now enjoy instant digital access to student progress. The app also provides dynamic reporting dashboards and mobile notifications, filling gaps in existing systems that lack real?time reporting and mobile integration. Data collection involved literature review, observation, and staff interviews. Overall, the application streamlines grading processes, ensures real?time updates, and significantly improves accuracy and efficiency.